Parental Beliefs About Returns to Educational Investments - The Later the Better? - Teodora Boneva; Christopher Rauh (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we study parental beliefs about the technology which maps parental investments into future child outcomes. We document that parents perceive late investments as more productive than early investments, and that they perceive investments in different time periods as substitutes. These beliefs contrast with findings in the empirical literature which suggest that early investments are more productive and are complementary to late investments. We show that parental beliefs about the returns to investments vary substantially across the population and that individual beliefs are predictive of actual investment decisions. Moreover, we document that parental beliefs about the productivity of investments differ significantly across socio-economic groups. Perceived returns to parental investments are positively related to household income, thereby potentially contributing to intergenerational earnings persistence.
Keywords: I26; I24; J13; 330